BIOSTRATIGRAPHY OF THE FRASNIAN STAGE BY RADIOLARIAN EVIDENCE - Afanas'eva M.S.; Aitchison J.C. (My University, 2001)
Revising Frasnian radiolarians, we established three new radiolarian zones within this stage. These are the Helenifore gogoense-Retisphaera concinna Zone of the lower Frasnian, Moskovistella allbororum-Ceratoikiscum ukhtensis Zone of the middle Frasnian. and Bientactinosphaera egindyensis-Polyentactinia cumretia Zone of the upper Frasnian.
Keywords: Frasnian; Devinian; Radiolarians; Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская::Верхний::Франский